Intra-trunk and arm coordination displayed by Olympic rowing athletes - Li, Y.; Koldenhoven, R. M.; Jiwan, N. C.; Zhan, J.; Liu, T. (Sports Biomechanics, 2021)
The purpose was to assess the intra-trunk and arm coordination of Olympic athletes during rowing on an ergometer. Rowing was performed at three stroke rates (18, 26, and 32 strokes/min). The sagittal plane motions of trunk segments and upper arm were collected for 59 Olympic athletes (32 females and 27 males) from the Chinese National Rowing Team. The coupling angles between the three pairs of segments (lumbar-pelvis, thorax-lumbar, upper arm-thorax) were generated using a vector coding method. The coupling angles were classified: in-phase, anti-phase, superior-phase, and inferior-phase. Three-way, mixed-model ANOVA were used to test the time spent in each coordination pattern. The trunk segments and upper arms demonstrated an in-phase coordination pattern for most of the time. During the drive phase, the time spent in in-phase was increased at higher stroke rates. Athletes are encouraged to use this in-phase pattern, especially between the pelvis and lumbar spine during training with high demands of stroke repetitions or time. During the recovery phase, the trunk segments were rotating mostly in-phase whereas the upper arm was flexing dominantly to maintain stroke length at higher stroke rates. Female and male rowers exhibited similar intra-trunk coordination patterns except for the upper arm-thorax pair.